Evidence of Phylogenetic Canalisation of the Circulating Platelet Mass in Man - von Behrens, W. E (Thrombosis and Haemostasis, 1972)
Phylogenetically mammalian platelets are an apocrine secretion from nucleated thrombocytes, and biologically the number of circulating fragments is irrelevant compared with their total mass and biochemical function. The literature on human genetic derangements affecting the circulating platelet mass is reviewed. The product of platelet count and platelet volume is shown to be “canalised” since many congenital forms of thrombocytopenia are associated with a reciprocal increase in the mean platelet volume. Considerations of platelet size are essential since macrothrombocytopenia is a racial characteristic of many Mediterranean peoples and probably also occurs frequently in others races. The location of platelet disorders in relation to the phylogenetic canal provides an objective classification which has diagnostic, therapeutic and prognostic significance.